2005
DOI: 10.1161/01.atv.0000148405.18071.6a
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin From Heme Oxygenase-1 Attenuates Vascular Endothelial Activation and Dysfunction

Abstract: Objective-Heme oxygenase-1 (HO-1), the rate-limiting enzyme of heme degradation, has recently been considered to have protective roles against various pathophysiological conditions. Since we demonstrated that HO-1 overexpression inhibits atherosclerotic formation in animal models, we examined the effect of HO modulation on proinflammatory cytokine production, endothelial NO synthase (eNOS) expression, and endothelium-dependent vascular relaxation responses. Methods and Results-After HO-1 induction by heme argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
155
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(165 citation statements)
references
References 29 publications
8
155
2
Order By: Relevance
“…33,34 Several investigators have found that the vascular-protective effects of HO can be reproduced by the administration of bilirubin or biliverdin, suggesting that the production of bilirubin is a major component of the vascular protection offered by HO. 8,25,28 Our result is similar to the inverse relationship reported between bilirubin level and CAD. 12,35 Two studies in this area are particularly noteworthy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…33,34 Several investigators have found that the vascular-protective effects of HO can be reproduced by the administration of bilirubin or biliverdin, suggesting that the production of bilirubin is a major component of the vascular protection offered by HO. 8,25,28 Our result is similar to the inverse relationship reported between bilirubin level and CAD. 12,35 Two studies in this area are particularly noteworthy.…”
Section: Discussionsupporting
confidence: 91%
“…Bilirubin inhibits inflammatory cytokine-induced endothelial cell expression of vascular cell adhesion molecule (VCAM)-1, 7 an initial step in atherosclerosis. 9 Bilirubin also inhibits monocyte transmigration, 25 prevents the formation of oxidized LDL, 26 inhibits endothelial inflammation and dysfunction, 8 inhibits vascular smooth muscle proliferation, 27 and prevents thrombus formation. 28 Human studies demonstrate that low bilirubin is associated with impaired endothelial function and increased carotid intima media thickness, 2 predictors of atherosclerosis, in healthy individuals free of cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1, expressed in the endothelium (39,40) and monocytes/macrophages (41), is upregulated upon exposure to reactive oxygen species, or oxidized LDL (42), and it antagonizes the pro-atherosclerotic processes through the actions of its catalytic end-products, carbon monoxide and bilirubin. It is of note that heme, either endogenous in hemorrhagic atherosclerotic lesions or derived from the denatured hemoglobin within them, significantly contributes to the lesion formation and potently induces HO-1 (30).…”
Section: Discussionmentioning
confidence: 99%
“…effects on vasculature. 4,5 Oxidative stress and inflammation are fundamental to the arteriopathy. 6 -8 Bilirubin was proven to act against plaque formation and subsequent atherosclerosis, 1 which was further confirmed by the studies revealing the relationships between bilirubin and peripheral artery disease (PAD) and carotid intima-media thickness (IMT).…”
Section: Introductionmentioning
confidence: 99%